2004
DOI: 10.1177/875512250402000103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Amiodarone Protocol and Management Clinic in Improving Adherence to Amiodarone Monitoring Guidelines

Abstract: To determine whether adherence to suggested monitoring parameters improved as a result of the development and implementation of an amiodarone protocol and management clinic. Adverse effects from amiodarone therapy were also evaluated to ascertain whether the Amiodarone Management Clinic (AMC) better identified adverse events as a result of improved monitoring.Methods: A retrospective review of charts of patients with an active amiodarone prescription was conducted. Patients were identified as enrolled in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Our results regarding monitoring are similar to others where depending on the tests chosen, both baseline testing and ongoing monitoring have largely been found to be inadequate, the reasons for these omissions have been discussed above 9,17 . Ongoing surveillance can be improved with dedicated clinics.…”
Section: Discussionsupporting
confidence: 84%
“…Our results regarding monitoring are similar to others where depending on the tests chosen, both baseline testing and ongoing monitoring have largely been found to be inadequate, the reasons for these omissions have been discussed above 9,17 . Ongoing surveillance can be improved with dedicated clinics.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are supported by other investigations, including a study by Graham et al, which showed that a centralized pharmacy service was not associated with universally improved adherence to amiodarone monitoring. 11 We also found that hospital admissions or ED visits for amiodarone-related ADEs occurred less often among patients enrolled in the AMS compared to control patients. It is noteworthy that thyroid events accounted for over half the total number of amiodarone-related ADEs.…”
Section: Discussionmentioning
confidence: 91%
“…15 The mean (SD) digoxin drug concentration was 0.87 (0.50), and the authors did not report any adverse effects related to digoxin use. The proportion of patients in the present study on concomitant digoxin was within the range reported in the study by Graham et al However, 1% of patients in the pharmacist-managed group and 2% in usual care had elevated digoxin concentrations and were either hospitalized or were seen in the ER.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…In contrast, a study that evaluated the effectiveness of an amiodarone management clinic (AMC) at a Veterans Affairs (VA) medical center found that 66% of patients in the AMC versus 37% in the comparison group were compliant with thyroid function monitoring within a year after initiating amiodarone. 15 They were also more likely to be compliant with liver function monitoring (69% vs. 38%).…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation